Physical fields as factors of natural processes in the works of the center for astrophysical research of North Kazakhstan University - Solodovnik, A.A.; Useinov, B.M.; Leontiev, P.I.; Gololobova, E.G. (Recent Contributions to Physics, 2023)
Some features of the approach to solving both purely practical and general theoretical problems based on the application of the field approach as a causal factor in the development of a number of phenomena are considered. In particular, when studying the genesis and evolution of mesospheric silvery clouds, the determining influence of a number of large-scale tropospheric processes on their development is consistently revealed. An original method of synthetic maps is proposed in this direction. Extensive statistical analysis of the cartographic material revealed that cyclonic activity, frontogenesis, development of occlusions and thunderstorm foci have a pronounced physical effect on the formation of silvery clouds over the northern hemisphere. The extraordinary results of the work stimulated further study of the influence of the temperature field of high latitudes in the southern hemisphere of the Earth – Antarctica – on the features of the seasonal evolution of the area of the global field of silvery clouds of the southern hemisphere. For the first time in research practice, statistically convincing evidence has been obtained that the surface temperature field is the leading factor in the formation of silvery clouds. This makes it possible, in turn, to consider silvery clouds as a significant marker of climate change. Along with this, longitude variations of the area of silvery clouds of the northern hemisphere of the Earth are considered. The results suggest the influence of geophysical fields on the genesis of such clouds. The question of the nature of gravitational and inert coupling is considered separately. A hypothesis has been put forward that allows not only to clarify the view of the nature of the inert mass, but also to estimate several general characteristics of the Universe relatively simply. The work is completed by a proposal to take a fresh look at the physical nature of information, based on the field method.